2017
DOI: 10.1523/jneurosci.2123-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Field Stimulation over Parietal Cortex Enhances Somatosensory Detection in Humans

Abstract: The role of neuronal oscillations in human somatosensory perception is currently unclear. To address this, here we use noninvasive brain stimulation to artificially modulate cortical network dynamics in the context of neurophysiological and behavioral recordings. We demonstrate that transcranial static magnetic field stimulation (tSMS) over the somatosensory parietal cortex increases oscillatory power specifically in the alpha range, without significantly affecting bottom-up thalamocortical inputs indexed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 39 publications
(26 reference statements)
2
48
1
Order By: Relevance
“…The effects of the static magnetic field intervention on behavioral indices have been confirmed in animal studies ( Saunders, 2005 ). Even in humans, the static magnetic field stimulation can alter sensory function ( Gonzalez-Rosa et al, 2015 , Carrasco-Lopez et al, 2017 ). Thus, it is possible that tsSMS can also modify human motor or sensory function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of the static magnetic field intervention on behavioral indices have been confirmed in animal studies ( Saunders, 2005 ). Even in humans, the static magnetic field stimulation can alter sensory function ( Gonzalez-Rosa et al, 2015 , Carrasco-Lopez et al, 2017 ). Thus, it is possible that tsSMS can also modify human motor or sensory function.…”
Section: Discussionmentioning
confidence: 99%
“…However, since static magnetic field stimulation induces only suppression of the motor system ( Oliviero et al, 2011 , Nojima et al, 2015 ), tSMS might not be useful for able-bodied people who want to improve motor behaviors, such as building muscle strength. A recent study reported that tSMS over the parietal cortex facilitated somatosensory detection ( Carrasco-Lopez et al, 2017 ). Thus, tSMS may be able to facilitate systems other than the motor system in both patients and able-bodied people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is potentially problematic, because it is known that both detection rate and excitability change over the course of an experiment. Specifically, behavioral measures such as hit rate (Boncompte et al, 2016;Carrasco-López et al, 2017) and sensitivity (Maniscalco et al, 2017) tend to decrease over time, possibly due to progressive fatigue, resulting from an exhaustion of cognitive resources. Likewise, ongoing α-power tends to increase over the course of an experiment (van Dijk et al, 2008), suggesting a decrease in excitability, possibly as a result of fatigue (Kaida et al, 2006).…”
Section: Within-trial Fluctuations Of Excitabilitymentioning
confidence: 99%
“…tSMS over the visual cortex also reduces the discomfort induced by high‐intensity light stimuli . Furthermore, tSMS over the parietal cortex has been found to enhance the detection of somatosensory stimuli . These findings suggest that the effect of tSMS might be strong enough to modulate human behavior, and may therefore have clinical applications.…”
Section: Introductionmentioning
confidence: 99%